On Caretta caretta's shell: first spatial analysis of micro- and macro-epibionts on the Mediterranean loggerhead sea turtle carapace. Issue 7 (14th September 2021) - Blasi, Monica Francesca; Rotini, Alice; Bacci, Tiziano; Targusi, Monica; Ferraro, Giusy Bonanno; Vecchioni, Luca; Alduina, Rosa; Migliore, Luciana
ABSTRACT: The loggerhead sea turtle, Caretta caretta (Linnaeus, 1758), is the most common sea turtle species in the Mediterranean Sea, where it can experience severe anthropogenic impacts. Although C. caretta is known to host more than 200 epibiotic taxa (crustaceans, algae and cyanobacteria), no reports have included a detailed evaluation of the microbial community of its carapace scutes. Thus, this study aimed to determine the diversity and composition of the visible and invisible communities on the carapace scutes of wild loggerhead turtles from the Aeolian Archipelago (Southern Tyrrhenian Sea, Italy) by using a combined approach of morphological/spatial examination and molecular analyses. Altogether, our results displayed a higher abundance of crustaceans, macroalgae and Proteobacteria on the posterior carapace scutes, while Firmicutes were more abundant on the anterior scutes. For the first time, this study showed the complexity of the microbial (invisible) and visible epibionts of the loggerhead sea turtles from the Mediterranean Sea and suggests the importance of including evaluation of the microbial components when studying epibiont communities.